A review of studies using hydrocarbon adsorption material for reducing hydrocarbon emissions from cold start of gasoline engine. (January 2021) - Han, Dandan; E, Jiaqiang; Deng, Yuanwang; Chen, Jingwei; Leng, Erwei; Liao, Gaoliang; Zhao, Xiaohuan; Feng, Changling; Zhang, Feng
Abstract: In order to improve engine performance by reducing hydrocarbon (HC) emissions from cold start of gasoline engine, firstly, cold-start emission control measures such as pre-treatment (including engine intake, fuel, and some engine timing parameters control studies to make air and fuel fully mixed and completely burned) and after-treatment (including oxidation of exhaust gas through the after-treatment system to reduce it to the atmosphere) are mainly summarized. Due to the particularity of the cold start conditions, engine after-treatment system can not be run in time, HC adsorption technology came into being. HC is adsorbed before after-treatment system functioning, and HC is not released until the after-treatment system works. In this paper, the experimental and simulation research on different adsorption materials (mainly including adsorption materials with different structure, size, heterogeneity, silicon to aluminum ratio and other parameters, different preparation and coating methods and different ion exchanged) used to control HC emission during cold start are summarized. Based on our work, the current research status of gasoline engine cold start HC control technology can be more clearly presented to relevant researchers. Through this article, the corresponding research results that have been obtained can be found more conveniently and comprehensively. And repeated research can be avoided well. At the same time, it is helpful for researchers to seek new research directions and paths for controlling the cold start HC emissions. The work done in this paper can effectively promote the further research and development of gasoline engine cold start HC emission control technology. Highlights: Cold start hydrocarbon emission control development are investigated. Limitations of engine pre-treatment and after-treatment are discussed. Hydrocarbon adsorbent materials in cold start are investigated. Hydrocarbon adsorbent catalysis in cold start is discussed. Hydrocarbon reduction measures for gasoline engine cold start are compared.